2018
DOI: 10.1101/341933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soluble CD93 is an Apoptotic Cell Opsonin Recognized by the αxβ2Integrin

Abstract: Abbreviations: ADAM -a disintegrin and metalloproteinase. BSA -bovine serum albumin. CHO -Chinese hamster ovary cells. CTLD -C-type lectin-like domain. FBS -fetal bovine serum. MMPmatrix metalloproteinase. PBMC -peripheral blood mononuclear cells. PFA -paraformaldehyde. sCD93 -soluble CD93. ABSTRACTEfferocytosis -the phagocytic removal of apoptotic cells -is essential for the maintenance of homeostasis and prevention of the inflammatory and autoimmune diseases which can follow the lysis of uncleared apoptotic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…DCXR encodes for a protein that plays an important role in glucose metabolism (36,37). CD93 is known as a myeloid marker involved in cell adhesion and clearance of apoptotic cells (38). The mechanism of mivebresib-induced modulation of these biomarkers remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…DCXR encodes for a protein that plays an important role in glucose metabolism (36,37). CD93 is known as a myeloid marker involved in cell adhesion and clearance of apoptotic cells (38). The mechanism of mivebresib-induced modulation of these biomarkers remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Our gene expression analysis identified a reduction in the expression of genes involved in the efferocytosis of apoptotic cells and the phagocytosis of microbial pathogens (Figures S4). RT-PCR confirmed that the αx integrin, a receptor for both complement-opsonized pathogens and CD93-opsonized ACs 48 , was downregulated in intima-infiltrating macrophages ( Figure 4A). Unexpectedly, integrin-linked kinase, which was downregulated in the patients analyzed in our microarray analysis ( Figure S4, Table S1) was not downregulated in the patient cohort used for our RT-PCR assays ( Figure 4B).…”
Section: Gata2 Overexpression Impairs Phagocytosis and Efferocytosismentioning
confidence: 80%
“…CFD is a serine protease required for the formation of C3 convertase. Soluble C1qR1/CD93 functions as a bridging molecule that aids apoptotic cell binding to professional phagocytes for removal by efferocytosis (Blackburn et al, 2019). Taken together, we provide validation for many injury-regulated gene products identified by scRNA-seq and show that serum proteins that function in opsonization feature prominently in the PNS following nerve crush injury.…”
Section: Resultsmentioning
confidence: 99%
“…CFD is a serine protease required for the formation of C3 convertase. Soluble C1qR1/CD93 functions as a bridging molecule that aids apoptotic cell binding to professional phagocytes for removal by efferocytosis (Blackburn et al, 2019).…”
Section: Identification Of Sciatic Nerve Injury Regulated Extracellul...mentioning
confidence: 99%